Towards Pragmatic Economic Policies: Economic Transformation and Industrialization for Revival of Zimbabwe in the New Dispensation Era - Charles Mazhazhate; Tapiwa C Mujakachi; Shakerod Munuhwa (International Journal of Engineering and Management Research, 2020)
Whilst literature has many monetary and economic policies that were enacted before and after the dawn of the New Dispensation in Zimbabwe the country still faces a downward trend in terms of economic recovery. This study reviews the various policies put in place by the government and their impact on socio-economic development of Zimbabwe. A review of Zimbabwe’s economic history shows that the country dropped from being one of the best economies in Sub-Saharan Africa and now ailing and characterised by hyperinflation, agricultural challenges, corruption, very high tax regime, huge domestic and foreign debts, increase in consumer prices and being a chief net importer of most goods or services. The study was underpinned by a case study survey from Singapore’s revival with both qualitative and quantitative instruments used. The study found out that even though the land reform had an impact on economic performance, corruption, party-power politics and absence of an economic institute eroded any necessary contribution to economic transformation and industrialization in Zimbabwe. The study also revealed that the bilateral and multi-lateral agreements that were enacted in the dawn of the new dispensation have not yielded the desired economic revival transformations. The study recommended establishment of an economic institute to direct policy as well as removal of unethical practices in both public and private sectors so as to ensure financial and economic discipline.